Cultural Impact on Adolescent Behavior Advancing Health, Gender: A Scoping Review - Dewi Purnamawati; Syamsulhuda Budi Musthofa; Farid Agushybana (Universitas Airlangga, 2024)
Background: Sexual and reproductive health is critical to the 2030 Sustainable Development Goals (SDGs). Various factors contribute to premarital sexual behaviour among adolescents, with culture being a pervasive influence in many countries. Adolescents in mountain communities are particularly vulnerable to engaging in premarital sexual behaviour. Aims: This review aims to explore research findings related to the cultural factors influencing premarital sexual behaviour among adolescents in general and specifically in mountain communities, contributing to the achievement of the SDGs. Method: This study employs a scoping review methodology. Search terms used in the articles include MeSH terms [